2018
DOI: 10.1088/1361-6528/aada29
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent, low-toxic and stable gradient-alloyed Fe:ZnSe(S)@ZnSe(S) core:shell quantum dots as a sensitive fluorescent sensor for lead ions

Abstract: In this paper, an aqueous-based approach is introduced for facile, fast, and green synthesis of gradient-alloyed Fe-doped ZnSe(S)@ZnSe(S) core:shell quantum dots (QDs) with intense and stable emission. Co-utilization of co-nucleation and growth doping strategies, along with systematic optimization of emission intensity, provide a well-controllable/general method to achieve internally doped QDs (d-dots) with intense emission. Results indicate that the alloyed ZnSe(S)@ZnSe(S) core:shell QDs have a gradient struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 61 publications
(74 reference statements)
1
14
0
Order By: Relevance
“…S6 and S7 for the experimental and calculated data) indicating that both Se 2and S 2incorporate similarly in the crystal lattice. After introduction of the ZnS shell, the diffraction peaks further shift to the cubic ZnS phase, which is consistent with previous reports [27,31]. 10):ZnSeS QDs was determined to be 2.4 nm ± 0.8 nm (Fig.…”
Section: Synthesis and Optical Properties Of Mn-doped Znses@2-mpa Qdssupporting
confidence: 92%
See 1 more Smart Citation
“…S6 and S7 for the experimental and calculated data) indicating that both Se 2and S 2incorporate similarly in the crystal lattice. After introduction of the ZnS shell, the diffraction peaks further shift to the cubic ZnS phase, which is consistent with previous reports [27,31]. 10):ZnSeS QDs was determined to be 2.4 nm ± 0.8 nm (Fig.…”
Section: Synthesis and Optical Properties Of Mn-doped Znses@2-mpa Qdssupporting
confidence: 92%
“…The formation of gradient alloyed ZnSe/ZnSeS with improved optical properties was also observed after the irradiation of thioacid-capped ZnSe QDs due to the light induced decomposition of the thiolbased ligand that generates S 2ions [26]. Due to their high stability and enhanced PL QYs, ZnSeS and core/shell ZnSeS/ZnS QDs have been demonstrated to be of high potential for lasers, sensing and bioimaging [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is no change in the fluorescence intensity of the beads incubated with Ca 2+ , K + , Cd 2+ , Mg 2+ , Ba 2+ , Co 2+ , Ni 2+ , and Na + ions. It has been reported that the fluorescence quenching of QDs toward Cu 2+ , Ag + , and Pb 2+ ions is attributed to the energy transfer (or electron transfer) of the QDs . Moreover, Figure b reveals that the fluorescence of the beads (incubated in the 1 × 10 −3 m Cu 2+ solution) gradually decreases with the incubation time, and finally the fluorescence completely disappears after incubation for 300 s. These results reveal that the fluorescence of the Mn‐doped ZnS QDs/alginate beads can be quenched by Cu 2+ and Ag + ions, and this fluorescence quenching can be adequately recognized by naked eyes even at an ion concentration of 1 × 10 −3 m .…”
Section: Resultsmentioning
confidence: 99%
“…20 Recently, selective sensing of copper ions has also been done using molybdenum disulde quantum dots. 21 Similarly, other researchers have also provided successful selective methods for the detection of other metal ions using different uorescent probes such as graphene oxide QDs, core-shell QDs and other carbon-based nanomaterials. [21][22][23][24][25] Chen and co-workers successfully synthesized and utilized water-soluble SiNPs as a nanosensor for the determination of potassium ferrocyanide and it can also be used to monitor the change in the pH of the solution.…”
Section: Introductionmentioning
confidence: 99%